2020
DOI: 10.1002/iub.2426
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐770 promotes oral squamous cell carcinoma migration and invasion by regulating the Sirt7/Smad4 pathway

Abstract: Oral squamous cell carcinoma (OSCC) is a common malignant cancer with unfavorable prognosis, and the epithelial‐to‐mesenchymal transition (EMT) is a critical contributor to OSCC metastasis. Recently, we have shown that sirtuin 7 (Sirt7) is associated with EMT and OSCC metastasis by acetylating small mother against decapentaplegic 4 (Smad4). Nonetheless, the mechanism of Sirt7 downregulation in OSCC cells remains unknown. This study analyzed the potential microRNAs that were predicted to regulate Sirt7 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It has been reported that dysregulation of miRNAs often leads to cancer occurrence ( Geng et al, 2018 ; Park et al, 2018 ). MiR-770 is known to have important biological functions in cancer tumorigenesis and metastasis ( Feng et al, 2019 ; Jia et al, 2020 ). Our current study found that miR-770 was significantly downregulated in exosomes, and it could suppress the migration and invasion of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dysregulation of miRNAs often leads to cancer occurrence ( Geng et al, 2018 ; Park et al, 2018 ). MiR-770 is known to have important biological functions in cancer tumorigenesis and metastasis ( Feng et al, 2019 ; Jia et al, 2020 ). Our current study found that miR-770 was significantly downregulated in exosomes, and it could suppress the migration and invasion of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oral cancer represents a relatively non frequent disease, largely preventable but burdened by a high mortality rate [ 74 ]. SIRT7 antagonizes oral cancer metastasis through the deacetylation of small mother against decapentaplegic 4 (Smad4) and can be found frequently downregulated in vivo because of miR-770 expression, whose expression represents a negative prognostic factor [ 75 ]. In oral squamous carcinoma cells Cal27, SIRT1 determines cell apoptosis affecting procaspase-3 and cyclin B1, ultimately exercising an anticancer effect [ 76 ]; additively, SIRT1 has been demonstrated to induce E-cadherin expression and to repress transforming growth factor-beta (TGF-β) interfering with the acquisition of the metastatic phenotype [ 77 ].…”
Section: Sirtuins and Cancermentioning
confidence: 99%
“…The length of the microRNA (miRNA/miR) is about 20 to 25 nucleotides, which have key regulatory functions in the occurrence or development of cancer, and can be involved in the regulation of tumor immune microenvironment 6 , cell migration, invasion and epithelial interstitial transformation 7 . MiR-770 promoted the migration and invasion of OSCC by regulating the Sirt7/Smad4 pathway 8 . MiR-487a-3p was found to inhibit the growth and invasion of OSCC by regulating the expression of PPM1A, thereby playing a tumor suppressor effect 9 .…”
Section: Introductionmentioning
confidence: 98%